Pendidikan Agama Islam: Fondasi Moral Spiritualitas Bangsa - Gani, Ainal; Oktavani, Mirtha; Suhartono, Suhartono (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
Islamic Religious Education plays a crucial role in building the morality and spirituality of the nation, especially in Indonesia, where the majority of the population is Muslim. Islamic Religious Education not only strengthens religious perspectives but also shapes the character of the younger generation to be virtuous. This study aims to explore Islamic Religious Education as the foundation of the nation’s moral and spiritual development. This research is a library study. The findings reveal that Islamic Religious Education significantly contributes to the development of individual morality and spirituality, in both religious, social, and cultural aspects. Islamic Religious Education teaches students to understand and practice Islamic teachings, with the aim of creating a pious and virtuous individual who contributes to society. Islamic Religious Education also teaches values of justice, mutual respect, and compassion, and supports the creation of a harmonious society that values diversity. Moreover, Islamic Religious Education functions to build moral awareness and social responsibility in individuals, enabling them to actively contribute to the advancement of the nation. This research reinforces the role of Islamic Religious Education in developing the religious character and devotion to God of the nation.